What do young children know about the differences between physical and mental objects? a study on preschoolers' ontological abilities. [article]. - Liwag, Ma. Emma Concepcion D. .
This study investigated urban Filipino preschool children's understanding of physical and mental entities, and whether they can apply the intuitive criteria of perceptual accessibility and public existence in ontologically distinguishing physical form mental phenomena. Ninety-one children aged 3,4, and 5, enrolled in 8 preschools in Metro Manila, participated in the experiment. A 3x3 factorial design treated age and ontological status (e.g., physical, mental,and hidden objects)as between-subject variables. The results showed that only the 5-year old children were able to consistently distinguished physical from mental entities, correctly asserting that physical objects can be seen and touched and have a public existence, while mental objects are not perceptually accessible and exist only in a person's mind.